Histopathological changes in different stages of alopecia areata - Ahmed, Z; Banik, RL; Paul, HK; Jaigirdar, QH; Begum, F; Chowdhury, SA (Mymensingh Medical Journal, 2010)
Mymensingh Med J. 2010 Jan;19(1):100-105. The abstract of this article is available on the PubMed website